2006
DOI: 10.1303/aez.2006.607
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of effects of transgenic Bt corn pollen on two non-target herbivorous beetles, Epilachna vigintioctopunctata (Coccinellidae) and Galerucella vittaticollis (Chrysomelidae)

Abstract: Laboratory bioassays were conducted to evaluate the effect of pollens from insecticidal transgenic Bt corn (event MON863) expressing Cry3Bb1 endotoxin on two native non-target herbivorous beetles, Epilachna vigintioctopunctata (Coccinellidae) and Galerucella vittaticollis (Chrysomelidae) larvae. Larvae were reared on leaf discs exposed to corn pollen for 10 days after hatching. G. vittaticollis had no adverse performance in terms of larval survival and development (proportion of larvae to third instar) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For the non-target non-EU chrysomelid species, Galerucella vittaticollis (the strawberry leaf beetle), Shirai (2006) reported that larval survival and development were not adversely affected when exposed to pollen from maize MON 863 at doses of 500 and 2,000 grains per cm 2 for ten days after hatching. The pollen density of 2,000 grains per cm 2 represents a worst-case exposure scenario, as several parameters affect the likelihood of environmentally relevant exposure in the field (reviewed by Perry et al, 2010;Perry, 2011).…”
Section: Non-target Chrysomelidsmentioning
confidence: 99%
“…For the non-target non-EU chrysomelid species, Galerucella vittaticollis (the strawberry leaf beetle), Shirai (2006) reported that larval survival and development were not adversely affected when exposed to pollen from maize MON 863 at doses of 500 and 2,000 grains per cm 2 for ten days after hatching. The pollen density of 2,000 grains per cm 2 represents a worst-case exposure scenario, as several parameters affect the likelihood of environmentally relevant exposure in the field (reviewed by Perry et al, 2010;Perry, 2011).…”
Section: Non-target Chrysomelidsmentioning
confidence: 99%